CHANGES IN OTHER ORGANS DUE TO THYROID CHANGES (Modern education and development, 2024)
Hormonal disorders of the thyroid gland, which are part of endocrinological diseases, are accompanied by hair loss, brittle nails, obesity, weight loss, stress, infertility, memory loss, and eye problems. It is recommended to consume iodized table salt to prevent thyroid diseases. Modern diagnostic methods for endocrinological diseases are being developed in the regions by providing endocrinology dispensaries with the necessary reagents.